Studies on the Association of GCK and GCKR Polymorphisms with Susceptibility to Gestational Diabetes Mellitus: A Meta-Analysis - Hongxia Tu; Youyi Zhang; Mingyi Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: A prevalent condition during pregnancy, gestational diabetes mellitus (GDM) affects a significant proportion of pregnancies worldwide and poses substantial risks to maternal as well as fetal health. Polymorphisms in the glucokinase (GCK) and glucokinase regulatory protein (GCKR) genes, which are crucial for glucose homeostasis, may modulate susceptibility to GDM. Hence, this meta-analysis aimed to assess the relationship between GDM and polymorphisms in GCK (rs1799884, rs4607517) and GCKR (rs780094, rs1260326). Methods: In this systematic review, we retrieved data from PubMed, EMBASE, Medline, EBSCO, Cochrane Library, and Chinese National Knowledge Infrastructure (CNKI) databases. Studies were critically appraised using the Newcastle-Ottawa Scale, and meta-analyses were performed using STATA 12.0. The odds ratios (ORs) were calculated with 95% confidence intervals (CIs) and heterogeneity was assessed with Cochran’s Q test as well as I2 statistical tests, respectively. Moreover, Begg’s test helped in evaluating publication bias. Results: We included 20 studies, comprising 9745 GDM women and 15,830 controls. All genetic models showed a strong correlation between the GCK rs1799884 polymorphism and GDM, with carriers of the A allele exhibiting an increased risk. Conversely, GCK rs4607517, GCKR rs780094, and rs1260326 were not significantly associated. However, heterogeneity was influenced by ethnicity and diagnostic criteria. Conclusions: The GCK rs1799884 polymorphism can be a potential predictive marker because it is significantly associated with an increased risk of GDM.